Impulse response analysis for Malaysian construction sector by vector error correction model - Khan, R.A. (Construction Research Institute of Malaysia, 2015)
The Malaysian construction sector (MCS) is a signiicant sector of the Malaysian economy. It plays a pivotal role in the social economic development. This study focusses on empirical examination of MCS, and develops a time series model equation for MCS under vector error correction (VEC) system. The estimated model is used to develop the impulse response functions (IRFs) to examine the behavior and response of MCS against the positive shocks produced in other major sectors of the economy and vice versa. The results suggest that the MCS is relatively small in size and contribution to GDP; however, it has strong correlation and long and short run association with all major sectors of the economy. The speed of adjustment of MCS toward long run equilibrium is 30 . It has positive response against the shock produced in other sectors of the economy except manufacturing sector. The most sensitive sector for MCS is mining and quarrying. The MCS economic activity is at peak in the third quarter of each year. This study is useful for government of Malaysia, economic planning unit, construction irms and other interested parties of the construction sect.or.